Music notation in the twentieth century: A practical guidebook - Stone, Kurt (New York W. W. Norton & Company, 1980)
In this comprehensive and definitive survey of current notation procedures, Kurt Stone has brought order to a field traditionally fraught with confusion and idiosyncrasy. He not only describes and recommends new methods for notating modern music, thereby establishing standard procedures for the present and future, but integrates them with traditional practices still in use. The result is a guide to all forms of notation used in serious music today.Stone is undoubtedly one of the world's leading authorities on contemporary music notation and its problems. As head of the Index of New Musical Notation, he collected and categorized the myriad new devices appearing in published music of this century. In collaboration with professional performers and conductors, he evaluated these devices in order to determine their effectiveness in practical application. At the International Conference on New Music Notation 1974, a consensus was sought from the eighty participating musicians from eighteen different countries. The results have been incorporated into this volume in the clearest and most direct way. Traditional notation is given detailed treatment, constituting, as it does, the basis for many of the innovative devices. The book is organized to facilitate the location of specific information and for easy reference. A minutely detailed index is provided as an additional and indispensable tool.